Melanoma in older patients: declining gap in survival between younger and older patients with melanoma. (2nd January 2020) - Schuurman, Melinda S.; Hollestein, Loes M.; Bastiaannet, Esther; Posthuma, Eduardus F.M.; van Akkooi, Alexander J.C.; Kukutsch, Nicole A.; Aarts, Maureen J.B.; Wakkee, Marlies; Lemmens, Valery E.P.P.; Louwman, Marieke W.J.
Abstract: Background: Older people have the highest incidence of melanoma and the population in most Western countries is ageing. We evaluated how the gap in incidence and survival between younger and older patients has developed during the past decades. Material and methods: All patients diagnosed with cutaneous melanoma between 1989 and 2015 ( n  = 84, 827) were identified from the Netherlands Cancer Registry. Elderly were defined as aged ≥70 years. Differences in patient and tumor characteristics were described, age-specific incidence rates were calculated, and relative survival (RS) and multivariable analyses estimating the Relative Excess Rate of dying (RER) were conducted Results: In older men, the melanoma age-standardized incidence increased from 18 to 103/100, 000 person-years (py) between 1989 and 2015 and in older women from 23 to 70/100, 000 py. In younger men and women, it increased from 8 to 21 and from 13 to 28/100, 000 py, respectively. Median Breslow thickness declined from 1.8 to 1.1 mm and from 1.6 to 1.1 mm in older men and women (2003 versus 2015), and from 1.1 to 0.9 mm and 0.9 to 0.8 mm in younger men and women. In older men, 5-year RS increased from 67% (95% CI: 63%–72%) in 1989–1997 to 85% (95% CI: 83%–87%) in 2007–2015 and in older women from 81% (95% CI: 78%–85%) to 89% (95% CI: 87%–91%). In younger men and women, RS increased from 82% (95% CI: 81%–83%) to 90% (95% CI: 90%–91%) and from 92% (95% CI: 92%–93%) to 96% (95% CI: 95%–96%). After case-mix correction, older men and women no longer showed an improved survival over time (RER 2010–2015 versus 2003–2009: 0.97; 95% CI: 0.81–1.16 and 0.95; 95% CI: 0.79–1.16). Whereas in younger men and women survival remained improved (RER 0.75; 95% CI: 0.67–0.83 and 0.77; 95%CI: 0.67–0.89). Conclusion: The gap in melanoma incidence between younger and older people is increasing due to a strong increase in incidence in older adults. Disparities in survival are declining, related to a narrowing gap in Breslow thickness.